Necessity of transformation political into the economic state - Anđelković, M.; Radosavljević, D.; Lilić, V. (Університет «КРОК», 2019)
From the emergence of the state as an institute to the present day, its goals and concepts of functioning have remained moreor less the same and have been reduced to organizing authority and population for defense against other tribes, later nations, but also to hold in obedience their subjects, i.e. those who are gave their rulers the mandate to govern on their behalf a unitycalled the state.States in modern conditions still function on the basis of the past, i.e., the past centuries. Instead of solving, the modern state produces problems and is unable to respond to new challenges and changes that occur both in the natural and social order. Evidence for this is obvious, ranging from environmental, political and social problems to migration, crises that are becoming more and more devastating, war conflicts, strikes and general discontent at national or global levels.In this context, the state creates mechanisms to maintain the status quo and extend the powers of the elected. Democracy, human rights protection, numerous global or regional declarations have become the subject of interpretation, as well as their disrespect, and even abuse. The trend of widening the gap between the poor and the rich is increasing, war conflicts have been waged in certain countries for years, many have been devastated, filled with huge amounts of poison that destroys the resource of water, land and air. Instead of great politicians and leaders like Roosevelt, De Gaulle, Churchill, political leaders and party officials who are hard to leave power and who are struggling to stay in power and rule for a long time, are on the scene.In a word, the modern state is unable to respond to a numerous challenges, because it has retained the same mechanisms and concepts of governance as i n the last century, and in many countries even from the time of the feudal age. Establishing force-based organizations, enacting laws, tax and parafiscal burdens to sustain party bureaucracy, feuds and enrichment on the one hand, and poverty and misery on the other, are visible in much of the world, indicating problems in the functioning of the state and government.Indicated condition can be improved by transforming a traditional political state into an economic state, whose priority goal would be to ensure a satisfactory quality of life and sustainable development. Thus, the state would focus on the people i.e. population, ratherthan the ideological political platform of the party in power.The paper indicates current issues of the functioning of the modern state and problems that are produced by the modern state.

Від виникнення держави як інституту до наших днів цілі та концепції функціонування залишилися більш-менш однаковими і зводилися до організації влади та населення для оборони проти інших племен, пізніших націй, але також і до утримання послух своїх підданих, тобто тих, хто дав своїм правителям мандат керувати від їх імені єдністю, що називається державою. Держави в сучасних умовах досі функціонують на основі минулого, тобто минулих століть. Замість того, щоб вирішувати, сучасна держава створює проблеми і не в змозі відповісти на нові виклики та зміни, що відбуваються як у природному, так і в суспільному порядку. Докази цього очевидні - від екологічних, політичних та соціальних проблем до міграції, криз, які стають все більш руйнівними, військових конфліктів, страйків та загального невдоволення на національному чи глобальному рівнях. У цьому контексті держава створює механізми для підтримки статусного кво та розширення повноважень обраних. Демократія, захист прав людини, численні глобальні чи регіональні декларації стали предметом тлумачення, а також їх неповаги та навіть зловживань. Тенденція до збільшення розриву між бідними та багатими зростає, конфлікти війни тривають у певних країнах протягом багатьох років, багато людей спустошені, наповнені величезною кількістю отрути, яка руйнує ресурс води, землі та повітря. Замість таких великих політиків і лідерів, як Рузвельт, Де Голль, Черчілль, політичні лідери та чиновники партії, яким важко покинути владу і котрі намагаються тривалий час залишатися при владі та правлячи. Одним словом, сучасна держава не в змозі відповісти на численні виклики, тому що вона зберегла ті самі механізми та концепції управління, як і минулого століття, а у багатьох країнах ще з часів феодальної епохи. Створення силових організацій, що приймають закони, податкові та парафіскальні тягарі для підтримання партійної бюрократії, ворожнечі та збагачення, з одного боку, і бідності та бідності з іншого, є видимими на більшій частині світу, що свідчить про проблеми у функціонуванні держави і уряд. Зазначена умова може бути покращена шляхом перетворення традиційної політичної держави в економічну державу, пріоритетною метою якої було б забезпечити задовільну якість життя та сталий розвиток. Таким чином, держава орієнтувалася б на народ, тобто населення, а не на ідеологічну політичну платформу партії при владі. У роботі вказуються актуальні питання функціонування сучасної держави та проблеми, які продукує сучасна держава.
Keywords: state; political state; economic state; state is the same as enterprise; держава; політична держава; економічний стан; держава - підприємство